Les espaces intermédiaires et la densification des tissus périurbains - Camille Benigni (Carnets de Géographes, 2014)
Our research focuses on the in-between spaces and their impact in the context of urban policies brought on the density. The densification is one of the goals of “compact and dense” city. What is the role of these spaces between the spheres of public and private in urban policies and procedures implemented in the territory ? We hypothesize that these architectural forms resulting practices are sustainable and installed in a logical part of the construction of suburban and residential areas. Give legitimacy to the in-between spaces which are invested by the people contributes to the construction of sustainable urban development for the development of territories, even if we know that the local legislative contexts and tools have a legal role in the investment opportunities of the plot. By analyzing the evolution of these in-between spaces on suburbs in Ile-de-France, we expect to better understand the process of densification of suburban fabric and their possible planning.